Thoracic aortic dissection in a patient with autosomal dominant polycystic kidney disease. - Adeola, T. (National Medical Association, 2001)
Autosomal dominant polycystic kidney disease is one of the most common hereditary diseases, and frequently has well defined extrarenal manifestations. Very few cases of aortic aneurysms associated with this disorder are described in literature. We report a 42-year-old male with autosomal dominant polycystic kidney disease presenting with dissecting aneurysm of the thoracic aorta.